Convergence rate of a proximal multiplier algorithm for separable convex minimization. (1st February 2017) - Sarmiento, O.; Papa Quiroz, E. A.; Oliveira, P. R.
Abstract: In this paper, we analyse the convergence rate of the proximal algorithm proposed by us in the article [A proximal multiplier method for separable convex minimization. Optimization. 2016; 65:501–537], which has been proposed to solve a separable convex minimization problem. We prove that, under mild assumptions, the primal-dual sequences of the algorithm converge linearly to the optimal solution for a class of proximal distances.